A new categorization of release models using a semi-analytic solution. (May 2015) - Kim, Myungbae; Choi, Byungil; Kim, Taehoon
Abstract: The spread of cryogenic liquid due to a limited period of release is investigated for the first time to clarify the unclear conventional concept regarding two release types: continuous and instantaneous release. The physical phenomenon is described by equations involving the volume, radius and height of the liquid pool, and there are three governing parameters: the evaporation rate per unit area, a release time, and a spill volume. As a result of the perturbation solutions, the combined model, which consists of the continuous model and the subsequent instantaneous model, is necessary for a large spill source rate, whereas the continuous model is only required for a small spill source rate. This combined release model is more realistic than the instantaneous release model, and it is shown that the combined model and the continuous model are clearly distinguished in the coordinate system of the release time and the spill volume using the analytical feature of the perturbation solution. Highlights: A new categorization of release models using a semi-analytic solution. The combined model that consists of continuous and subsequent instantaneous model required for large spill source rate. Only the continuous model required for small spill source rate. Clear distinction between two a continuous release and a combined release.